ДЕРЖАВНЕ ФІНАНСУВАННЯ СФЕРИ КУЛЬТУРИ ЯК ЧИННИК ФОРМУВАННЯ ТА РОЗВИТКУ СУСПІЛЬНОЇ СВІДОМОСТІ УКРАЇНЦІВ - Сіренко, Світлана Сергіївна (Науковий журнал «Світ фінансів», 2017)
Сіренко С. С. Державне фінансування сфери культури як чинник формування та розвитку суспільної свідомості українців. Обґрунтовано зв’язок між державною фінансовою підтримкою сфери культури і процесами формування сталого суспільства, зокрема суспільної свідомості українців. Визначено, що державне фінансування є одним із чинників подібних процесів. Доведено необхідність державного фінансування сфери культури, наведено аналіз ситуації з цього питання в деяких країнах світу та в Україні, систематизовано існуючі моделі фінансування сфери культури, виявлено доцільність тих чи інших джерел фінансування культури і мистецтва. Визначено два основних змістових тлумачення сфери культури: з позиції економічної теорії – як галузі виробництва; з позиції теорії фінансів – як інвестиції в майбутнє нації і країни. Сиренко С. С. Государственное финансирование сферы культуры как фактор формирования и развития общественного сознания украинцев. Обосновано связь между государственной финансовой поддержкой сферы культуры и процессами формирования устойчивого общества, в частности общественного сознания украинцев. Определено, что государственное финансирование является одним из факторов подобных процессов. Обоснована необходимость государственного финансирования сферы культуры, приведен анализ ситуации по этому вопросу в некоторых странах мира и в Украине, систематизированы существующие модели финансирования сферы культуры и выявлена целесообразность тех или иных источников финансирования культуры и искусства. Определены две основные содержательные трактовки сферы культуры: с позиции экономической теории – как сферы производства; с позиции теории финансов – как инвестиции в будущее нации и государства. Sirenko S. State funding of culture as a factor in the formation and development of public consciousness of Ukrainians. During the active development of post-industrial society observed strengthening the role of information, knowledge and emotions. Culture in its nature contains all these components. Therefore, in civilized countries culture gradually occupies a leading position in the market of intangible benefits. Usually it is an indicator of a high level of society, its consciousness, education, sustainability. In such conditions becomes actuality both the state support of cultural sphere in Ukraine, as the developing of mechanisms for its implementation. The purpose – to determine the impact of the state funding of culture on the formation and development of social consciousness. We conducted work on determination of necessity of state sponsorship of industry of culture, analyzed situations through this question in some countries of the world and in Ukraine, existent models over of financing of industry of culture and exposure of expediency of those or other sources of funding culture and art are here brought. It is determined that the cultural sphere has two interpretations from a position of our study. First – from a position of the economic theory – as a field that aims at creating of a cultural product that can be bought or sold. Second – from a position of the theory of finance – it is the impact of cultural products that created for the formation of moral and spiritual human guise, his attitude towards the world and the events that occur; in other words – the funding of culture is equivalent investment in the future of the nation and the state.